Fatores que influenciam a tomada de decisão por stakeholders envolvidos na governança colaborativa : um estudo de caso do programa Todos Somos Porto Alegre - Callegaro, Sabrina (2020)
Collaborative Governance is a governmental mechanism that involves parts of collective decision-making oriented by consensus, intending to implement public policy. Contemporary problems, often complex, use the implementation of structures aimed at cooperation so that there are or involve different actors so that decisionmaking is transparent and consistent. Research on Collaborative Governance investigates antecedents, processes, results, number and diversity of actors involved, therefore there is an opportunity to explore the topic from the perspective of decision making, consequently, to understand the process of decision-making, one exploratory qualitative research was developed. This research focuses on analyzing the factors related to the multi-stakeholder decision-making process. The research question to be answered is: What factors influence decision-making in a Collaborative Governance process? Based on the research question and the literature review, a project by the Porto Alegre City that has the characteristics of a Collaborative Governance arrangement was chosen as a case study. The data collection was interviews with stakeholders involved in the decision-making process and analysis of the project main documents. The results support the proposal of a framework with the factors that influence decision making, Systemic Understanding, Relationship between stakeholders, Decision Orientation, Bureaucracy, Complexity and Power, increasing the understanding of the theme and enabling a deeper understanding of the decisionmaking process in Collaborative Governance. Comprehend the models and theories about decision making are crucial to meet the demands of society, consequently, the factors that influence decision making can be a reference for the implementation of collaborative processes, enabling the definition of the strategy to be adopted.